Some considerations in reference to the establishment of the Office of a Public Trustee in Ireland - O'Connell, John Robert (Statistical and Social Inquiry Society of Ireland, 1913)
The large amount of public interest which has been aroused in many quarters by the creation of the office of Public Trustee in England, and the very reasonable demand for a detailed examination of that official's sphere of operations; and of his mode of administering the functions imposed on him by the Public Trustee Act, 1906, will, I hope, be accepted as my excuse for reading this paper before you tonight.
Read Friday, 25th April, 1913.
Keywords: Public Trustee; New Zealand; 314.15